2021
DOI: 10.1210/clinem/dgab701
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Growth in Children With Classic Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency During Adrenarche and Beyond

Abstract: Context Patients with classic congenital adrenal hyperplasia (CAH) often fail to achieve their full growth potential. Adrenarche may accelerate bone maturation and thereby result in decreased growth in CAH. Objective To analyze the impact of growth during adrenarche on final height of adequately treated classic CAH patients. Design Retrospective, multi-center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…A second meta-analysis of 35 studies conducted between 1966 and 2007 showed an average FH SDS of -1.38 and a corrected FH SDS of -1.03 ( 16 ). A recent study reported mean FH SDS values of -0.4 to -1.4 ( 17 23 ). Good compliance, early diagnosis (age <1 year), and short duration of HDC treatment in the peripubertal period reportedly improved FH ( 15 , 19 , 20 , 22 ).…”
Section: Goals Of 21-ohd Treatment In Childhoodmentioning
confidence: 97%
See 4 more Smart Citations
“…A second meta-analysis of 35 studies conducted between 1966 and 2007 showed an average FH SDS of -1.38 and a corrected FH SDS of -1.03 ( 16 ). A recent study reported mean FH SDS values of -0.4 to -1.4 ( 17 23 ). Good compliance, early diagnosis (age <1 year), and short duration of HDC treatment in the peripubertal period reportedly improved FH ( 15 , 19 , 20 , 22 ).…”
Section: Goals Of 21-ohd Treatment In Childhoodmentioning
confidence: 97%
“…Nonetheless, whatever the definition, several studies reported less pubertal height gain in patients with 21-OHD than in a population of healthy subjects ( 17 , 24 29 ). The latest study, in which all the subjects received a diagnosis of 21-OHD in the neonatal period, demonstrated that the pubertal growth spurt was similar to that of healthy children of both sexes ( 23 ). This apparently normal pubertal development suggests that early diagnosis via newborn screening enabled normalization of pubertal height gain and FH.…”
Section: Goals Of 21-ohd Treatment In Childhoodmentioning
confidence: 99%
See 3 more Smart Citations